Training Method for Secondary School Teachers as Readers - Valdivia Yábar, Silvia Verónica; Tineo Quispe, Luis Enrique (Journal of higher education theory and practice, 2023)
The teaching of literary reading remains organized around activities that hide the subjectivity of the reader. However, several researchers affirm that all reading is subjective and that the involvement of the reading subject would stimulate personal reactions and plural readings. In this framework, the objective of this study was to understand the effects of a teaching method of comprehensive work on the training of future teachers of Spanish in a program of studies at the Universidad Nacional del Altiplano in Peru. The qualitative research approach, the type of explanatory research, and the quasi-experimental design were adopted. A teacher trainer directed the didactic sequence, organized in seven sessions. The subjective investment of eight voluntary participants was observed and interpreted to understand how to better train them in literary reading and teaching. The results allowed us to identify the subjective resources mobilized by the teachers and to observe the modalities of the reflexivity of the students in the oral and written productions.